Citrus Black Spot - Megan M. Dewdney; Natalia A. Peres (EDIS, 2010)
PP274, a 2-page illustrated fact sheet by Megan M. Dewdney and Natalia A. Peres, provides a visual reference for symptoms of this fungal disease affecting all commercial cultivars of citrus. Published by the UF Department of Plant Pathology, May 2010.